2014
DOI: 10.1111/exd.12501
|View full text |Cite
|
Sign up to set email alerts
|

Meaning of relative gene expression in multilayered cultures of epidermal keratinocytes

Abstract: Reconstructed human epidermis (RHE) has become an in vitro model of choice for studying cell and tissue functions. Analysis of gene expression over the course of reconstruction must take into account the heterogeneous differentiation states of keratinocytes reconstituting the typical epidermal layers. In monolayer cultures, relative mRNA expression levels of differentiation markers are usually expressed as a ratio versus a classical reference gene (also named house-keeping gene) tested to be expressed equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…Recently, ITGA6 has been identified as a differentiation depended RG in organotypic cell cultures that is selectively expressed in the basal layer of the epidermis . Our results are in line with those of Malaisse and co‐workers, showing that the relative expression of ITGA6 decreases during differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, ITGA6 has been identified as a differentiation depended RG in organotypic cell cultures that is selectively expressed in the basal layer of the epidermis . Our results are in line with those of Malaisse and co‐workers, showing that the relative expression of ITGA6 decreases during differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…With respect to the bound lipid profile, this is similar to that of native human skin (Ponec et al, 2003) however, it must be stated that measurements of this profile have been conducted with a lower level of precision. Furthermore, the presence of a leaky cornified envelope would also contribute to a reduced skin barrier property; while almost no data have been reported to date on the protein composition of the cornified envelope in HSEs, it has been shown that some cornified envelope proteins are expressed differently (involucrin) in the models as compared to native human skin (Malaisse et al, 2014).…”
Section: Tab 1: Models For Dermal Absorptionmentioning
confidence: 99%
“…Epidermal proteins analysed in this work have been selected from tissue microarray data available in the Human Protein Atlas database (http://www.proteinatlas.org) or from the literature. More precisely, the following proteins were described in some studies as specifically expressed in a single epidermal layer: LFNG, ITA6, KLK14, KLK5, KLK7, PRSS8, PAR2, RFNG [17][18][19][20][21], CADH3 [22], TGM1 [23], K2C5, K1C14, K1C10, H6VRG3, TGM2, INVO, LORI, SPRR4, CRNN, FILA [24], E9PBK1 [25], VDR, CP27B [26]. Liver proteins expressed preferentially in periportal or perivenous epatocytes were selected based on previous works [15,16,27 -29].…”
Section: Identification Of Protein Markersmentioning
confidence: 99%